The Use of Educational Technologies for Creative Teaching in South African Technology Classrooms : A Social Constructivist Approach - Nkosi, Praygod Bonginkosi; Ramaligela, Sylvia Manto (Universitas Pendidikan Mandalika, 2025)
This study aims to explores how Technology teachers enhance their Creative Teaching Skills by integrating Educational Technologies into their classroom practices. This study followed a qualitative research approach where a case of seven teachers enrolled for honours degree were sampled. Qualitative thematic analysis was used for the data which was collected through non-participatory observation. Through a Social Constructivism frame, the findings of this study indicate that through the planning and presentation of several lessons, the teachers showed great improvement in the integration of Educational Technologies into their classroom practices. Teachers gained knowledge and skills about the integration of Educational Technologies for planning and presenting creative lessons. This finding suggests that the teachers developed Creative Teaching Skills, gained experience, and transformed their classroom practices. Lack of policy, infrastructure, and resources in rural public schools was also discovered to be a hindrance to teachers' inability to integrate Educational Technologies into their teaching. This finding suggests that teachersâ€™ proper training in technology integration alone is not a panacea to effective technology integration for Creative Teaching in the classroom. Therefore, it is recommended that for Creative Teaching through technology integration to flourish in the classroom, it needs to be considered along matters of ICT policy development and implementation as well as ICT infrastructure development in schools. Â Integration of Educational Technologies with the Creative Teaching Skills of Technology teachers were invigorated with knowledge facts as they gained insights during their participation in the multiple planning and presentation of creative lessons.